Case Report: Primary Intraosseous Poorly Differentiated Synovial Sarcoma of the Femur - Pang, Ke; Guo, Xiaoning; Jiang, Yi; Xu, Lina; Ling, Lin; Li, Zhihong (Frontiers in Oncology, 2022)
Primary poorly differentiated intraosseous synovial sarcoma is exceedingly rare. Here we present a case of primary poorly differentiated intraosseous synovial sarcoma from the proximal femur in a 16-year-old female. The case was initially misdiagnosed but the correct diagnosis of synovial sarcoma was eventually confirmed by fluorescence in situ hybridization and next-generation sequencing. We review the literature pertaining to synovial sarcoma, and show that this case is the second molecularly proven poorly differentiated intraosseous synovial sarcoma in the literature. Recognition of intraosseous synovial sarcoma composed of small round cells is imperative in order to avoid misdiagnosis of the tumor as Ewing sarcoma and other small round cell tumors, all of which have markedly different clinical management.